Feasibility and Efficacy of Nurse-Driven Acute Stroke Care. - Mainali, Shraddha; Stutzman, Sonja; Sengupta, Samarpita; Dirickson, Amanda; Riise, Laura; Jones, Donald; Yang, Julian; Olson, DaiWai M. (Journal of Stroke & Cerebrovascular Diseases, 2017)
Background: Acute stroke care requires rapid assessment and intervention. Replacing traditional sequential algorithms in stroke care with parallel processing using telestroke consultation could be useful in the management of acute stroke patients. The purpose of this study was to assess the feasibility of a nurse-driven acute stroke protocol using a parallel processing model.Methods: This is a prospective, nonrandomized, feasibility study of a quality improvement initiative. Stroke team members had a 1-month training phase, and then the protocol was implemented for 6 months and data were collected on a "run-sheet." The primary outcome of this study was to determine if a nurse-driven acute stroke protocol is feasible and assists in decreasing door to needle (intravenous tissue plasminogen activator [IV-tPA]) times.Results: Of the 153 stroke patients seen during the protocol implementation phase, 57 were designated as "level 1" (symptom onset <4.5 hours) strokes requiring acute stroke management. Among these strokes, 78% were nurse-driven, and 75% of the telestroke encounters were also nurse-driven. The average door to computerized tomography time was significantly reduced in nurse-driven codes (38.9 minutes versus 24.4 minutes; P < .04).Conclusions: The use of a nurse-driven protocol is feasible and effective. When used in conjunction with a telestroke specialist, it may be of value in improving patient outcomes by decreasing the time for door to decision for IV-tPA.